Emotion recognition and brain mapping for sentiment analysis: a review - Hulliyah, Khodijah; Awang Abu Bakar, Normi Sham; Ismail, Amelia Ritahani (Institute of Electrical and Electronics Engineers Inc., 2018)
The rapid growth of the Internet has caused the increase in the amount of textual information available, such as in blogs, discussion forums and review sites on the web, where the texts surely have the emotion content. Emotion is one appearence of people behaviour and it is an important performance in human computer interaction (HCI). Human express the emotion in the form of facial expression, speech and writing text. Recently, researchers in computational linguistic (CL) areas are interested in the attention of emotion for Sentiment Analysis (SA). SA naturally observes the emotion conveyed by a text, and at the same time, distinguishing positive and negative valence. The wide areas of CL research, actually considerable for investigating the emotion dimension detection and searching the approaches and techniques in the term of emotion recognition (ER). There are two significant trends of research in the area, the emotion recognition based on state affective computing and the real time using brain signal machines. The two areas have the same aim for getting the improvement result in sentiment analysis with the mapping of emotion recognition provided. The exclusive work on emotion detection is comparatively rare and lacks empirical evaluation research. This paper provides the overview of past and recent research on emotion detection as well as some approaches and techniques used and shows the linked between both SA and ER.